Efficient Electrochemical Nitrate Reduction to Ammonia with Copper‐Supported Rhodium Cluster and Single‐Atom Catalysts. Issue 23 (5th April 2022) - Liu, Huimin; Lang, Xiuyao; Zhu, Chao; Timoshenko, Janis; Rüscher, Martina; Bai, Lichen; Guijarro, Néstor; Yin, Haibo; Peng, Yue; Li, Junhua; Liu, Zheng; Wang, Weichao; et al.
Abstract: The electrochemical nitrate reduction reaction (NITRR) provides a promising solution for restoring the imbalance in the global nitrogen cycle while enabling a sustainable and decentralized route to source ammonia. Here, we demonstrate a novel electrocatalyst for NITRR consisting of Rh clusters and single‐atoms dispersed onto Cu nanowires (NWs), which delivers a partial current density of 162 mA cm −2 for NH3 production and a Faradaic efficiency (FE) of 93 % at −0.2 V vs. RHE. The highest ammonia yield rate reached a record value of 1.27 mmol h −1  cm −2 . Detailed investigations by electron paramagnetic resonance, in situ infrared spectroscopy, differential electrochemical mass spectrometry and density functional theory modeling suggest that the high activity originates from the synergistic catalytic cooperation between Rh and Cu sites, whereby adsorbed hydrogen on Rh site transfers to vicinal *NO intermediate species adsorbed on Cu promoting the hydrogenation and ammonia formation. Abstract : A novel copper nanowire supported rhodium cluster and single‐atom electrocatalyst (Rh@Cu) for nitrate reduction reaction (NITRR) was designed. Benefiting from the catalytic cooperation between Rh and Cu, whereby Rh activates the hydrogenation of the *NO intermediate on Cu, Rh@Cu systems achieve a Faradaic efficiency up to 93 % at −0.2 V vs. RHE and a record ammonia yield rate of 1.27 mmol h −1  cm −2 .